A low-entropy ordered alloy@metallic glass core-shell catalyst based on the recycling of waste ternary lithium batteries and its preparation method and application
By recycling waste ternary lithium battery materials and using Joule heating process to prepare graphite-loaded α3M low-entropy orderly alloy @MxPy metal glass core-shell catalyst, the problems of agglomeration and activity inactivation of the cathode catalyst of lithium air battery during high-temperature calcination are solved, the high reactivity and stability of the catalyst are achieved, and the electrochemical performance of lithium air battery is improved.
Patent Information
- Application Number
- CN202410624065.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-05-20
AI Technical Summary
The cathode catalysts of existing lithium air batteries are prone to particle agglomeration during high-temperature calcination, reduced dispersion of active sites, and affected catalytic activity and selectivity. At the same time, they are prone to shedding and corroded by strong oxidative electrolyte during long-term cycles, resulting in premature inactivation of the activity.
By recycling graphite and NiCoMn materials in waste ternary lithium batteries, a graphite-loaded α3M low-entropy ordered alloy @MxPy metal glass core-shell catalyst is prepared by using Joule heating technology to achieve uniform small-size distribution of the catalyst and the construction of high reactive sites.
It improves the electrochemical performance of lithium air batteries, enhances catalytic activity and stability, extends the cycle life of the catalyst, reduces the generation of by-products, and inhibits the passivation phenomenon on the positive electrode surface.
Smart Images

Figure CN118577281B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cathode catalysts for lithium-air batteries, and in particular to a graphite-supported α3M low-entropy ordered alloy @M based on the recycling of waste ternary lithium batteries. x P y Metallic glass core-shell catalyst and its preparation method and application. Background Art
[0002] Compared with lithium-ion batteries, lithium-air batteries have irreplaceable advantages. First, lithium-ion batteries are limited by the amount of lithium stored in the positive and negative electrode materials themselves, and their theoretical energy density is limited, while lithium-air batteries have a theoretical energy density of 3500Wh kg. -1 The ultra-high theoretical energy density is much higher than that of traditional lithium-ion batteries. Secondly, the production of lithium-ion batteries is cost- and resource-dependent. Lithium-air batteries are safer than lithium-ion batteries to a certain extent.
[0003] According to the reaction principle of lithium-air batteries (2Li+O2→Li2O2), the discharge product Li2O2 will be generated and decomposed through oxygen reduction (ORR) reaction and oxygen evolution (OER) reaction respectively. However, superoxide (O 2- ) and singlet oxygen ( 1 O2), causing the electrolyte and carbon cathode to decompose, generating byproducts that are not easy to decompose, such as Li2CO3, HCOOLi, and CH3COOLi. In addition, due to the insulation and insolubility of Li2O2, it will also cause deposition. The accumulation of these products during the cycle may lead to the passivation of the cathode, thus slowing down the ORR and OER reaction kinetics, resulting in problems such as excessive overpotential and poor cycle stability.
[0004] In order to solve the above problems, researchers have developed many advanced lithium-air battery cathode catalysts, such as transition metal oxides, carbon-based materials, single atoms, perovskites, precious metals and other catalysts. However, the preparation of these catalysts often requires high-temperature calcination. Excessive temperatures and long-term heat preservation often lead to agglomeration of catalyst particles, reduce the dispersion of active sites, and affect their catalytic activity and selectivity. On the other hand, during long-term cycles, these catalysts are easy to fall off and are easily corroded by strong oxidizing electrolytes, resulting in premature deactivation of the catalyst activity. These have limited the development of lithium-air battery technology. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the preparation of cathode catalysts for lithium-air batteries often needs to be completed by means of high-temperature calcination. Excessive temperature and long-term heat preservation often lead to agglomeration of catalyst particles, reduce the dispersion of active sites, and affect their catalytic activity and selectivity. On the other hand, during long-term circulation, these catalysts are easy to fall off and are easily corroded by strong oxidizing electrolytes, resulting in premature deactivation of catalyst activity. All of these limit the development of lithium-air battery technology.
[0006] To solve the above problems, the present invention firstly recovers the negative electrode graphite and the valuable metal M (NiCoMn) in the positive electrode of the waste ternary lithium battery, and then prepares the graphite-supported α3M low-entropy ordered alloy @M by Joule heating process. x P y Metal glass core-shell catalyst, wherein α is a Pt-based noble metal, which is one of Pt, Ir, Ru, and Rh, and M is one of three NiCoMn transition metals. The recycled graphite negative electrode material is used as a carbon carrier, the NiCoMn ions after the positive electrode material is recovered are used as a transition metal source, and the Pt-based noble metal salt is used as a noble metal source. The four metals of Pt, Ni, Co, and Mn are prepared together by the Joule heating process. The surface of the alloy nanocrystals is then amorphized by secondary Joule heating, and an amorphous M is constructed on its outer layer. x P y "Metallic glass". The graphite-supported α3M low-entropy ordered alloy @M x P y Metallic glass core-shell catalysts are used in lithium-air batteries to effectively improve the electrochemical performance of lithium-air batteries.
[0007] To achieve the above purpose, the present invention is mainly realized by the following technical means: a graphite-loaded α3M low-entropy ordered alloy @M based on the recycling of waste ternary lithium batteries x P y The preparation method of the metallic glass core-shell catalyst comprises the following steps:
[0008] (1) Graphite powder recovered from waste ternary lithium batteries, NiCoMn solution and zinc nitrate are mixed in an organic solvent, and Pt-based noble metal salt is added as a noble metal source. The mixture is stirred evenly, centrifuged and vacuum dried to obtain a precursor powder; wherein the zinc nitrate solution is used as a graphite exfoliation blasting point, so that while the graphite carbon is loaded with α, Ni, Co and Mn metal ions, the blocky graphite carbon is exfoliated into two-dimensional nanosheets by utilizing the characteristic that zinc nitrate is easily pyrolyzed at high temperature.
[0009] (2) The precursor powder is placed in a Joule heating device and kept at a temperature of 2000-3500°C for 15-20 seconds, and then rapidly cooled to room temperature within 5-10 seconds to obtain a graphite-supported α3M low-entropy ordered alloy, i.e., α3M alloy powder. This transient high temperature constructed in a short period of time can make the α atoms and M (M = NiCoMn) metal atoms arrange regularly to form an α3M low-entropy ordered alloy.
[0010] (3) The carbon-supported alloy nanoparticles are mixed evenly with triphenylphosphite and hexadecylamine, mechanically ground, and sent to a Joule heating device for secondary Joule heating to obtain graphite-supported α3M low-entropy ordered alloy @M x P y Metallic glass core-shell catalyst, where α is a Pt-based noble metal, one of Pt, Ir, Ru, and Rh, and M is one of three NiCoMn transition metals. A layer of amorphous M is coated on the surface of the alloy nanoparticles by phosphating. x P y "Metallic glass" obtained graphite-supported α3M low-entropy ordered alloy @M x P y Metallic glass core-shell catalyst. By regulating the Joule heating process, the synergistic effect of internal alloy nanocrystals and external metallic glass is achieved to enhance the catalytic activity, thus constructing a bifunctional catalyst for lithium-air batteries.
[0011] The Joule heating transient thermal shock method used in the present invention can effectively improve the problems in the preparation process of the existing lithium-air battery cathode catalyst, so that the catalyst has a smaller size and a more uniform dispersion, thereby providing more reactive sites, promoting proton and electron transport, and improving reaction kinetics. At the same time, the present invention relates to the constructed graphite-supported α3M low-entropy ordered alloy @M x P y Metallic glass core-shell catalysts can maintain long-term structural stability. The core of the catalyst is an alloy nanoparticle composed of α atoms and M (M = Ni, Co, Mn) metal atoms arranged in an orderly manner, and the shell is M x P y Amorphous metallic glass layer. Among them, α3M alloy nanocrystals and M x P y The amorphous layer serves as the main reactive site for ORR and OER reactions, while the M x P yOn the basis of adjusting the internal electronic structure and coordination environment, the amorphous layer can also fully expose the reaction active sites, protect the internal α3M alloy nanocrystals from oxidation, dissolution, and precipitation, and maintain the long-term stability of the active components. At the same time, the synergistic effect of the two components helps to balance the adsorption, reaction, and desorption behaviors of oxygen-containing reactants and intermediates at the surface sites, thereby promoting the formation and decomposition of Li2O2, reducing the formation of by-products, and inhibiting the passivation phenomenon of the positive electrode surface, thereby improving the OER and ORR reaction kinetics.
[0012] Furthermore, the graphite powder and NiCoMn solution are recovered from waste ternary lithium batteries.
[0013] Furthermore, the above recycling process includes the following steps:
[0014] (0-1) Recycling of graphite negative electrodes from waste ternary lithium batteries: Cut the negative electrodes after stripping and place them in an N-methylpyrrolidone solution for ultrasonic treatment. The resulting turbid liquid is washed with hydrochloric acid, then washed with deionized water, centrifuged, and vacuum dried to obtain the recovered graphite powder.
[0015] (0-2) Recovery of NiCoMn positive electrodes of waste ternary lithium batteries: Cut the stripped positive electrodes and place them in an N-methylpyrrolidone solution for ultrasonic treatment. Centrifuge and dry the obtained turbid liquid to obtain battery black powder containing Li, Ni, Co, and Mn. Place the battery black powder in an oxalic acid solution, oil bath, and then centrifuge to obtain Ni, Co, and Mn oxalate precipitates that do not contain lithium impurities. Add the precipitates to a nitric acid solution and filter to obtain a solution containing NiCoMn ions.
[0016] At present, the global lithium-ion battery market is worth about $48 billion, and it is expected to rise to $182.53 billion by 2030. The growing electric vehicle market will continue to expand the production demand for lithium-ion batteries. However, the number of discarded lithium-ion batteries is also surging, and it is estimated that the global discarded lithium-ion batteries will reach 1.2 million tons in 2030. Therefore, the recycling of waste lithium-ion batteries is a key means to achieve a sustainable battery economy. At present, the main means of recycling waste lithium-ion batteries include pyrometallurgy, hydrometallurgy, biometallurgy, solvent metallurgy, etc. Although the technology of waste battery recycling has matured in some aspects, there is still room for improvement in improving the recovery rate, reducing technical costs, and reducing environmental pollution and safety hazards.
[0017] The present invention can process waste lithium-ion batteries to achieve efficient recovery of high-value metals such as nickel, cobalt, manganese and graphite carbon materials, reduce the exploitation of natural resources, and can re-apply the recycled raw materials to lithium-air batteries to achieve the purpose of resource integration and reuse; in addition, compared with traditional pyrometallurgical technology, the present invention has lower energy consumption and emissions, reduces environmental pollution; and the process flow is relatively simple, has a wide range of applicability, and can achieve stable and efficient waste battery recycling.
[0018] At the same time, this method chooses to reuse the recycled raw materials from waste batteries into lithium-air batteries, which can reuse retired high-value metals, allowing lithium-air batteries to reduce costs while ensuring long battery life, thereby improving their competitiveness in the electric vehicle market.
[0019] Further, in step (1), 500-1500 mg of graphite powder and 0.5-1 mL of 10 mg / mL zinc nitrate solution are added to 100 mL of acetonitrile and mixed evenly, and NiCoMn solution and Pt noble metal salt solution are added thereto at a molar ratio of 1:9, and the total volume of NiCoMn solution and Pt noble metal solution is controlled to be 10-15 mL. Adding the metal salt solution according to the molar ratio can just form alloy nanoparticles of α3M configuration, and controlling the above volume parameters can make the alloy nanoparticles evenly distributed on the graphite carbon matrix.
[0020] Furthermore, the Pt-based noble metal salt solution is one of platinum acetylacetonate solution, iridium acetylacetonate solution, ruthenium acetylacetonate solution, and rhodium triacetylacetonate solution, or a mixture of more than one of them.
[0021] Furthermore, step (1) uses magnetic stirring, centrifuges after stirring for 4 hours, and then vacuum-dries at 60-80° C. for 24 hours to obtain a precursor powder. Stirring for 4 hours can allow the precursor solution to react fully. Stirring time that is too short will result in incomplete reaction, and stirring time that is too long will result in particle agglomeration. Vacuum-drying at 60-80° C. for 24 hours can fully dry the precursor powder.
[0022] Furthermore, in step (3), the α3M alloy powder is fully mixed with triphenylphosphite and hexadecylamine in a mass ratio of 5:1:1. Mixing in this ratio can cause the alloy particles to be surface phosphated instead of being completely phosphated.
[0023] Furthermore, in step (3), the mechanical grinding is performed for 30-60 minutes, the Joule heating parameters are 800-1500°C for 15-20 seconds, and then rapidly cooled to room temperature within 5-10 seconds to obtain graphite-supported α3M@M x P y Core-shell catalyst. Controlling the above heating and cooling rates can make the arrangement of α atoms inside the α3M alloy nanoparticles tend to be ordered, while the arrangement of M atoms tends to be disordered.
[0024] A graphite-supported α3M@M prepared by any of the above methods x P y Core-shell catalyst. The size of the α3M low-entropy ordered alloy nanoparticles synthesized by this method is about 2-15nm, and the content of α3M low-entropy ordered alloy nanoparticles is 1%-10%. This ultra-small size is conducive to maximizing the catalytic activity of α3M alloy nanocrystals and improving the utilization rate of α metals; and through strict control of temperature and insulation time, the arrangement of metal atoms in the alloy nanocrystals can be manipulated, and the coordination environment and electronic structure between α atoms and M (Ni, Co, Mn) metal atoms can be adjusted; in addition, this transient thermal shock method can also induce lattice distortion while inducing orderly diffusion of metal atoms, generating a large number of defects, thereby increasing the reaction active sites and effectively improving the catalytic activity.
[0025] Moreover, the present invention alloys the noble metal α with the transition main group metal M (Ni, Co, Mn) to form α3M low entropy ordered alloy nanoparticles, which overcomes the problem of insufficient catalytic activity of a single noble metal. This structure is to insert transition main group metal M atoms in order in two adjacent layers of Pt atoms, respectively, to achieve an ordered arrangement of Pt and M, but inside the M position, the three transition metals Ni, Co, and Mn are in a randomly mixed state. Therefore, the characteristics of combining ordered atomic arrangement and disordered atomic arrangement in one also make the α3M low entropy ordered alloy nanoparticles have a unique coordination environment and electronic structure, enhance catalytic activity and stability, and can effectively solve the problems of severe polarization and poor cycle stability of lithium-air batteries.
[0026] A graphite-supported α3M@M x P y Application of core-shell catalyst in lithium-air battery. x P y Metallic glass protective layer for α3M low entropy ordered alloy@M x P y The metallic glass core-shell catalyst further plays a key role in achieving high catalytic activity and high structural stability. Different from the traditional method of using a tubular furnace to calcine at high temperature to purge the phosphorus-containing gas flow or using hydrothermal solvent thermal reaction, this method uses the Joule heating process to construct M x P y Metallic glass, the thickness of the metallic glass can be adjusted by controlling the amount of triphenylphosphite and hexadecylamine and the phosphating time, M x P yThe thickness of the metallic glass protective layer is controlled to be 0.5-3nm. Within this range, the surface will not be enriched with a large amount of phosphorus components due to excessive thickness, which will weaken the exposure of the alloy nanocrystals, nor will the oxidation, dissolution, and precipitation of the alloy nanocrystals be alleviated due to too low thickness. In addition, the metallic glass effectively adjusts the coordination environment and electronic structure of the alloy nanocrystals, further enhances the degree of defects, optimizes the adsorption of oxygen-containing intermediates, greatly improves the catalytic activity of the ordered alloy nanocrystals, and enhances the electrochemical performance of lithium-air batteries.
[0027] The beneficial effects of the present invention are:
[0028] (1) Advantages of Joule heating process: Conventional high-temperature annealing can usually promote the rearrangement of metal atoms and the interaction of dd orbitals, but it is very easy to cause particle agglomeration and uneven size distribution, affecting the catalytic activity of the reaction process. This method uses rapid Joule thermal shock to evenly anchor α3M alloy nanoparticles on the surface of graphite carbon matrix. The extremely fast heating and cooling rates and short-term ultra-high temperature retention of this technology can achieve uniform small-size distribution of α3M alloy nanoparticles, promote the orderly arrangement of atoms and the construction of rich defects, enhance the metal-support interaction, fully stimulate the catalytic activity, and thus improve the catalytic ability and stability.
[0029] (2) Advantages of low-entropy ordered alloys: Since the atomic diffusion in the rigid lattice has a high activation barrier and the bonds between metal atoms need to be destroyed, the atomic arrangement of alloy nanoparticles changes from disorder to order very slowly from a kinetic point of view. The rapid Joule thermal shock technology used in this method will reduce the atomic diffusion activation energy of α3M, thereby achieving a precise and orderly atomic structure between α and M. At the same time, the three elements Ni, Co, and Mn are mixed at the M position to form an α3M low-entropy ordered alloy. This intermetallic compound that combines ordered and disordered atomic arrangements can optimize the electronic structure, thereby improving the conductivity and electron transport properties; at the same time, there are a large number of lattice distortions on its surface. These rich active sites serve as key sites for oxygen reduction (ORR) / oxygen evolution (OER) reactions, which are conducive to the adsorption and dissociation of oxygen molecules and intermediates, and effectively improve the ORR / OER reaction efficiency.
[0030] (3) Advantages of metallic glass: The metallic glass produced on the surface of α3M alloy nanoparticles by the second Joule heating phosphating can well maintain the structure of the internal low-entropy ordered alloy α3M, effectively slowing down the dissolution and precipitation of α3M, stabilizing the crystalline phase structure of the inner layer, and thus improving the stability of the catalyst. In addition, the active sites of crystalline materials often only exist on the surface, while amorphous materials have reactive sites on the surface and in the volume confinement at the same time. In addition, metallic glass has abundant defects and flexible shapes, which help to cause lattice strain effects and improve catalytic activity. Finally, the unique structure of metallic glass can adjust the coordination environment and local electronic structure, expose more reactive sites, and move the d-band center, thereby optimizing the adsorption energy, increasing the discharge product yield, and promoting the ORR / OER reaction kinetics.
[0031] (4) Advantages of core-shell catalysts: This method uses a two-step Joule heating strategy to prepare the core first and then the shell, constructing a core-shell catalyst with highly controllable surface morphology and interface structure. This unique structural feature can provide abundant active sites and highly dispersed catalytic centers, and can provide an effective surface protection layer, which helps to extend the cycle life of lithium-air batteries; in addition, the pore structure and interface effect of the graphite-supported core-shell catalyst help increase the diffusion rate of oxygen on the material surface, reduce the proton and electron transfer impedance during the reaction process, and improve the catalytic rate of lithium-air batteries.
[0032] (5) This method is universal. By changing the type of noble metal α salt (α = platinum salt, iridium salt, ruthenium salt, rhodium salt), a series of graphite-supported α3M@M x P y catalyst.
[0033] (6) The raw materials of this method are widely available, low in price, simple to synthesize, highly repeatable, and highly applicable, and are suitable for industrialized production. Waste ternary lithium batteries can also be recycled. Once the metals such as Ni, Co, and Mn rich in the positive electrode materials of waste ternary lithium batteries leak into the natural environment, they will cause decades of pollution to water sources and soil, and the graphite in the negative electrode materials will also cause dust pollution. The valuable Ni, Co, Mn and graphite can be recycled by treating waste ternary lithium batteries with this method, and the recovery rate and purity are high, which is conducive to the renewable utilization of waste resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 :Graphite-supported Pt3M@M x P y Spherical aberration-corrected transmission electron microscopy high-angle annular dark-field image of the core-shell catalyst.
[0035] Figure 2 :Graphite-supported Pt3M@M x Py X-ray powder diffraction curves of core-shell catalysts.
[0036] Figure 3 :Graphite-supported Pt3M@M x P y Complete charge and discharge performance curves of lithium-air batteries with core-shell catalysts.
[0037] Figure 4 :Graphite-supported Pt3M@M x P y Lithium-air battery cycling performance diagram of core-shell catalysts. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] All raw materials in the examples of the present invention, unless otherwise specified, are commercially available.
[0040] Embodiment 1:
[0041] A graphite-supported α3M low-entropy ordered alloy@M x P y The preparation method of the metallic glass core-shell catalyst comprises the following steps:
[0042] (1) mixing graphite powder, NiCoMn solution and zinc nitrate solution in an organic solvent, adding Pt-based noble metal salt as a noble metal source, stirring evenly, centrifuging and vacuum drying to obtain a precursor powder;
[0043] (2) placing the precursor powder in a Joule heating device, keeping it at a temperature of 2000-3500° C. for 15-20 seconds, and then rapidly cooling it to room temperature within 5-10 seconds to obtain a graphite-supported α3M low entropy ordered alloy, i.e., α3M alloy powder;
[0044] (3) The carbon-supported alloy nanoparticles are mixed evenly with triphenylphosphite and hexadecylamine, mechanically ground, and sent to a Joule heating device for secondary Joule heating to obtain graphite-supported α3M low-entropy ordered alloy @M x P y Metallic glass core-shell catalyst, wherein α is a Pt-based noble metal, which is one of Pt, Ir, Ru, and Rh, and M is three NiCoMn transition metals.
[0045] Embodiment 2:
[0046] Step (1) 500-1500 mg of graphite powder and 0.5-1 mL of 10 mg / mL zinc nitrate solution are added to 100 mL of acetonitrile and mixed evenly, and NiCoMn solution and Pt-based noble metal salt solution are added thereto in a molar ratio of 1:9, and the total volume of the NiCoMn solution and the Pt-based noble metal solution is controlled to be 10-15 mL.
[0047] The rest are the same as in Example 1.
[0048] Embodiment 3:
[0049] In step (1), the Pt-based noble metal salt solution is one of a platinum acetylacetonate solution, an iridium acetylacetonate solution, a ruthenium acetylacetonate solution, and a rhodium triacetylacetonate solution, or a mixture of more than one of them.
[0050] The rest are the same as in Example 1 or 2.
[0051] Embodiment 4:
[0052] In step (1), magnetic stirring is adopted, and after stirring for 4 hours, centrifugation is performed, and then vacuum drying is performed at 60-80° C. for 24 hours to obtain a precursor powder.
[0053] The rest are the same as any one of Examples 1-3.
[0054] Embodiment 5:
[0055] Step (3) The α3M alloy powder is fully mixed with triphenylphosphite and hexadecylamine in a mass ratio of 5:1:1.
[0056] The rest are the same as any one of Examples 1-4.
[0057] Embodiment 6:
[0058] Step (3) mechanical grinding for 30-60 minutes, Joule heating parameters are 800-1500°C for 15-20 seconds, and then rapidly cooled to room temperature within 5-10 seconds to obtain graphite-supported α3M@M x P y Core-shell catalysts.
[0059] The rest are the same as any one of Examples 1-5.
[0060] Embodiment 7:
[0061] In step (1), the graphite powder and NiCoMn solution are recovered from waste ternary lithium batteries, and the recovery process includes the following steps:
[0062] (0-1) Recycling of graphite negative electrodes from waste batteries: Cut the negative electrodes after stripping and place them in an N-methylpyrrolidone solution for ultrasonic treatment. The resulting turbid liquid is washed with hydrochloric acid, then washed with deionized water, centrifuged, and vacuum dried to obtain the recovered graphite powder.
[0063] (0-2) Recovery of NiCoMn positive electrodes from waste batteries: Cut the stripped positive electrodes and place them in an N-methylpyrrolidone solution for ultrasonic treatment. Centrifuge and dry the resulting turbid liquid to obtain battery black powder containing Li, Ni, Co, and Mn. Place the battery black powder in an oxalic acid solution, oil bath, and then centrifuge to obtain Ni, Co, and Mn oxalate precipitates that do not contain lithium impurities. Add the precipitates to a nitric acid solution and filter to obtain a solution containing NiCoMn ions.
[0064] The rest are the same as any one of Examples 1-6.
[0065] Verification results:
[0066] Depend on Figure 1 It can be seen that after the rapid impact of Joule heating, zinc acetate evaporates after reaching the decomposition temperature, causing the blocky graphite carbon matrix to be peeled off into sheets. This sheet structure helps to load the alloy nanoparticles, expose more active sites, and is also conducive to the full infiltration of the electrolyte, accelerating the reaction kinetics. At the same time, α3M@M x P y The size of the core-shell nanoparticles is very uniform, with a particle size of about 8nm; the surface of the α3M ordered alloy nanoparticles is coated with a layer of 1-2nm M x P y Amorphous layer, the above proves that α3M@M x P y Successful preparation of core-shell catalysts.
[0067] Depend on Figure 2 It can be seen that α3M@M x P y The X-ray powder diffraction pattern of the core-shell catalyst conforms to the standard card of Pt3Co, indicating that the construction of metallic glass does not completely phosphate the alloy nanoparticles. In addition, superlattice diffraction peaks (100), (110), (210), and (211) appear in the diffraction peaks, indicating that α3M@M x P y The crystal structure is an ordered intermetallic compound.
[0068] Depend on Figure 3 It can be seen that α3M@M x P y Core-shell catalysts are used in lithium-air batteries with a limited current of 200 mAg -1 Deep charge and discharge, discharge capacity up to 12342.48mAh g-1 , the overpotential is as low as 0.57V, and the charging voltage is basically stable at around 3.2V. It can be inferred that α3M@M x P y It fully improves the Li2O2 yield, improves its discharge capacity, and effectively reduces the polarization of OER, showing excellent electrochemical performance.
[0069] Depend on Figure 4 As can be seen, in the limit 1000mAh g -1 Capacity, 400mAg -1 When the current is applied, it can stably cycle for 337 h, indicating that α3M@M x P y The core-shell catalyst has structural stability, can reversibly produce and decompose the discharge product Li2O2, and has excellent cycle stability.
[0070] In summary, this method uses a two-step Joule heating strategy to prepare the core first and then the shell to construct a core-shell catalyst with highly controllable surface morphology and interface structure. This unique structural feature can provide abundant active sites and highly dispersed catalytic centers, and can provide an effective surface protection layer, which helps to extend the cycle life of lithium-air batteries; in addition, the pore structure and interface effect of the graphite-supported core-shell catalyst help increase the diffusion rate of oxygen on the surface of the material, reduce the proton and electron transfer impedance during the reaction process, and improve the catalytic rate of lithium-air batteries, which has broad market prospects.
[0071] The above description is only a simpler and better embodiment of the present invention and is not intended to limit the present invention. Any modification, replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A graphite-supported α3M low-entropy ordered alloy based on the recycling of waste ternary lithium batteries@M x P y A method for preparing a metallic glass core-shell catalyst, characterized in that The following steps are involved: (1) Graphite powder, NiCoMn solution and zinc nitrate solution are mixed together in an organic solvent, and a Pt-based noble metal salt is added as a noble metal source, stirred evenly, centrifuged and vacuum dried to obtain a precursor powder; that is, 500-1500 mg of graphite powder and 0.5-1 mL of a 10 mg / mL zinc nitrate solution are added to 100 mL of acetonitrile and mixed evenly, and NiCoMn solution and Pt-based noble metal salt solution are added thereto in a molar ratio of 1:9, and the total volume of the NiCoMn solution and the Pt-based noble metal solution is controlled to be 10-15 mL; (2) placing the precursor powder in a Joule heating device, keeping it at a temperature of 2000-3500° C. for 15-20 seconds, and then rapidly cooling it to room temperature within 5-10 seconds to obtain a graphite-supported α3M low entropy ordered alloy, i.e., α3M alloy powder; (3) The carbon-supported alloy nanoparticles are fully mixed with triphenylphosphite and hexadecylamine in a mass ratio of 5:1:1, mechanically ground for 30-60 minutes, and then sent to a Joule heating device for secondary Joule heating. The Joule heating parameters are 800-1500°C for 15-20 seconds, and then rapidly cooled to room temperature within 5-10 seconds to obtain a graphite-supported α3M low entropy ordered alloy @M x P y Metallic glass core-shell catalyst, wherein α is a Pt-based noble metal, which is one of Pt, Ir, Ru, and Rh, and M is three NiCoMn transition metals.
2. The preparation method according to claim 1, characterized in that: The graphite powder and NiCoMn solution are recovered from waste ternary lithium batteries.
3. The preparation method according to claim 2, characterized in that The recycling process comprises the following steps: (0-1) Recycling of graphite negative electrodes from waste ternary lithium batteries: Cut the negative electrodes after stripping and place them in an N-methylpyrrolidone solution for ultrasonic treatment. The resulting turbid liquid is washed with hydrochloric acid, then washed with deionized water, centrifuged, and vacuum dried to obtain the recovered graphite powder. (0-2) Recovery of NiCoMn positive electrodes of waste ternary lithium batteries: Cut the stripped positive electrodes and place them in an N-methylpyrrolidone solution for ultrasonic treatment. Centrifuge and dry the obtained turbid liquid to obtain battery black powder containing Li, Ni, Co, and Mn. Place the battery black powder in an oxalic acid solution, oil bath, and then centrifuge to obtain Ni, Co, and Mn oxalate precipitates that do not contain lithium impurities. Add the precipitates to a nitric acid solution and filter to obtain a solution containing NiCoMn ions.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The Pt-based noble metal salt solution is one of a platinum acetylacetonate solution, an iridium acetylacetonate solution, a ruthenium acetylacetonate solution, and a rhodium triacetylacetonate solution, or a mixture of more than one of the above.
5. The preparation method according to any one of claims 1 to 3, characterized in that: In step (1), magnetic stirring is adopted, and after stirring for 4 hours, centrifugation is performed, and then vacuum drying is performed at 60-80° C. for 24 hours to obtain a precursor powder.
6. A graphite-supported α3M@M prepared by any method of claims 1-5 x P y Core-shell catalysts.
7. A graphite-supported α3M@M as claimed in claim 6 x P y Application of core-shell catalysts in lithium-air batteries.
Citation Information
Patent Citations
Method for recycling positive electrode of waste ternary lithium battery and alkaline hydrogen evolution application
CN117702182A
Method for preparing carbon-loaded noble metal / transition metal cross-scale catalyst and application
CN118039937A